Matrix effects on plant-frugivore and plant-predator interactions in forest fragments - Herrera, José M; García, Daniel; Morales, Juan M (Landscape ecology, 2011)
Structural features of both habitat remnants and surrounding matrix can be important for explaining plant population dynamics and ecosystem functions in human-impacted landscapes. However, little is known about how the structural features of the adjacent matrix affect biotic interactions and whether such context effects are subject to temporal variations. Using the hawthorn Crataegus monogyna in northern Spain, we studied matrix effects on two sequential plant-animal interactions, frugivory by birds and postdispersal seed predation by rodents. Using Hierarchical Linear Models, we compared the magnitude of both interactions on trees located in two patch types that strongly differed in structural features of the adjacent matrix habitat: patches totally surrounded by a degraded, structurally contrasted pastures (unconnected patches), and trees growing in patches adjacent to a lowly degraded, structurally similar mature forests (connected patches). We compared outcomes for 2005 and 2006, which were years with strong differences in community-wide fruit and seed abundance. Frugivory rate did not differ between patch types in either year, likely related to high mobility of birds. Seed predation rates were higher in unconnected patches than in connected ones, but only in 2005. We conclude that strong interannual fluctuations in resource availability are not rare in temperate systems and that recruitment rates could be frequently reduced within unconnected patches, thus collapsing plant regeneration processes of hawthorn populations. Overall, our results suggest that generalizations about potential effects of the matrix on plant-animal interactions within remnant patches must consider: (1) species-specific habitat responses of the organisms, (2) suitability of neighbouring habitats in terms of food supply, and (3) temporal variations in plant-resource availability for interacting animals.